Principles of imaging subsurface magnetic susceptibility with application to synthetic and field examples - MOHAMED, Hassan (Contributions to Geophysics and Geodesy, 2025)
In this study, a simple new methodology for imaging subsurface magnetic susceptibility from three-dimensional (3-D) correlation tomography of magnetic data is presented. This methodology can be used to rapidly evaluate the equivalent subsurface magnetic susceptibility distribution, especially when powerful commercial programs are unavailable. In correlation tomography, the region of interest is divided into a regular 3-D grid, and the correlation is then calculated between the measured magnetic field data and the computed magnetic field data resulting from a magnetic point dipole. A probabilistic estimate of the distribution of the equivalent magnetic dipoles can be achieved using the correlation coefficient technique. The coefficient values range between −1 and +1 and are equivalent physical parameters. The cross-correlation values obtained at different depth intervals are plotted to show that the higher the correlation coefficient, the greater the equivalent magnetic dipole distribution and vice versa. The computer program was tested on both synthetic magnetic data and on real field data acquired over the west Garida and Hamama deposits in Egypt's Eastern Desert. Overall, the cross-correlation tomography approach yields quick, efficient results that can be used as a basis for subsequent in-depth modelling.